(untitled) - United Nations Economic Commission for Europe (New York, 1983)
An important way farmers can conserve energy is making efficient use of fertilizers and other nutrient sources. This book will introduce farmers to the concepts of fertilizer energy and efficient nutrient use. It discusses how to optimize fertilizer use by soil testing, fertilizer placement, and application and by using farm manures and cover crops as part of a soil fertility plan. It includes a discussion on the impact of nutrient carry-over and crop rotation on fertility planning. Thoughtful use of these management practices will help farmers conserve energy and save money.
Keywords: Cây trồng,Crops; Dinh dưỡng,Hội nghị,Nutrition,Congresses